Pengaruh Kompetensi Badan Pengawas, Budaya Organisasi Dan Sistem Pengendalian Internal Terhadap Pencegahan Fraud - I Gusti Ayu Made Novi Ariskayanti; Ni Komang Sumadi (Hita Akuntansi dan Keuangan, 2023)
Preventing fraud is a measure taken to lessen the likelihood that dishonest individuals will deceive others for financial gain. The research team wanted to know if there was a correlation between a strong internal control system, a strong corporate culture, and a low incidence of fraud. This investigation was carried out at the North Denpasar District Village Offices. A total of 66 people were polled for this study's samples. To gather information, we'll be using a questionnaire. In the meantime, the outer and inner PLS models are used in the data analysis procedure. According to the results of the simulations, the effectiveness of fraud prevention measures is enhanced by the competence of the supervisory body. A company's culture can make a big difference in how effectively it combats fraud. When it comes to preventing fraud, the internal control system plays a crucial role.